Analisis dan Perancangan Sistem Informasi Pengarsipan Dokumen Dengan Pendekatan Berorientasi Objek (Studi Kasus : Dinas Sekretariat Dewan, Pemerintahan Kota Batu) - Cindy Retno Dewati; Ismiarta Aknuranda; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This research analyzes and designs a Document Archiving Information System to deal with problems in document archive management that still uses manual methods and is not computerized which causes documents to be prone to damage or loss in the event of a disaster such as fire or flood at the House of Regional People's Representative Assembly Secretariat in Batu City. This information system is analyzed and designed using the Object Oriented Analysis and Design (OOAD) approach by conducting business process modeling, requirements analysis, system design, and evaluating the system using the Traceability method and prototype testing to system users. The results of this study are the current and proposed business process models, requirement analysis which includes 15 features, 12 functional requirements, 3 non-functional requirements, 1 actor, and 5 use cases. The results of this system design consist of system architecture, use case analysis, design elements, sequence diagram design, class design, database design, interface design and prototype design. The evaluation results using Traceability show that all requirements are properly defined and have a unique code so that each functional requirement and design can be tracked easily and the results of evaluation of prototype testing are the flow of all scenarios that are expected by the user, and the prototype is run in accordance on system use case specifications.